Thin films of poly[(9,9-dioctylfluorene)-co-thiophene] deposited on ITO by the Langmuir–Schaefer and Langmuir–Blodgett techniques - Bento, Danielly Cristina; Barbosa, Camila Gouveia; Roncaselli, Lucas Kaique Martins [UNESP]; Renzi, Wesley; Duarte, José Leonil; de Almeida Olivati, Clarissa [UNESP]; Péres, Laura Oliveira; de Santana, Henrique (Springer Nature, 2017)
The copolymer, poly[(9,9-dioctylfluorene)-co-thiophene] (PDOF-co-Th), prepared by the Suzuki reaction, was deposited as thin films on ITO substrates using the Langmuir–Blodgett and Langmuir–Schaefer techniques. The optical properties of the films were studied by UV–Vis reflectance, photoluminescence and time-resolved photoluminescence, and the electrical properties by electrochemical impedance spectroscopy as a function of film thickness. Raman spectroscopy and atomic force microscopy (AFM) were also used with the aim of elucidating the interactions between layers and the morphology of the PDOF-co-Th thin films at the interface with the ITO. The absorption and emission spectra showed shifts and alterations in the intensities of the bands as a function of film thickness, related to the formation of aggregates and increases in the radiation self-absorption effect. The Nyquist and Bode phase diagrams revealed that the charge transfer process at the ITO/PDOF-co-Th/electrolyte interfaces was enhanced as the number of layers increased. Raman spectra of monolayer films revealed a preferential interaction between the fluorine rings and the electrode surface that was not strong enough to alter the optical and electrical properties of the copolymer. However, as shown in the AFM images of the PDOF-co-Th film surfaces, there is an increase in roughness and compaction that proves that the material agglomerates as the number of layers increases, suggesting that the thiophene rings also come closer together on the substrate surface, enhancing the charge transfer process at this interface.